Systemic Edwardsiella tarda infection in a Western African lungfish (Protopterus annectens) with cytologic observation of heterophil projections. Issue 9 (8th June 2018) - Rousselet, Estelle; Stacy, Nicole I.; Rotstein, David S.; Waltzek, Tom B.; Griffin, Matt J.; Francis‐Floyd, Ruth
Abstract: This report describes a case of systemic bacterial infection caused by Edwardsiella tarda in a Western African lungfish ( Protopterus annectens ) exposed to poor environmental and husbandry conditions. The fish presented with a large, external ulcerative lesion and died 2 weeks after developing anorexia. Histological evaluation revealed multifocal areas of necrosis and heterophilic and histiocytic inflammation throughout multiple tissues. Gram stain identified small numbers of intra‐ and extracellular monomorphic Gram‐negative 1 to 2 μm rod‐shaped bacilli. Cytology of lung granuloma, kidney and testes imprints identified heterophilic inflammation with phagocytosis of small monomorphic bacilli and some heterophils exhibiting cytoplasmic projections indicative of heterophil extracellular traps (HETs). Initial phenotypic analysis of isolates from coelomic fluid cultures identified E. tarda . Subsequent molecular analysis of spleen, liver and intestine DNA using an E . tarda ‐specific endpoint PCR assay targeting the bacterial fimbrial subunit yielded a 115 bp band. Sequencing and BLASTN search revealed the sequence was identical (76/76) to E . tarda strain FL95‐01 (GenBank acc.CP011359 ) and displayed 93% sequence identity (66/71) to Edwardsiella hoshinae strain ATCC 35051 (GenBank acc.CP011359 ). This is the first report of systemic edwardsiellosis in a lungfish with concurrent cytologically identified structures suggestive of HETs.